2023
DOI: 10.3390/medicina59040762
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hyperbaric Oxygen Therapy in the Treatment of Surgical Site Infections: A Narrative Review

Abstract: Surgical site infections (SSIs) are among the most prevalent postoperative complications, with significant morbidity and mortality worldwide. In the past half century, hyperbaric oxygen therapy (HBOT), the administration of 100% oxygen intermittently under a certain pressure, has been used as either a primary or alternative therapy for the management or treatment of chronic wounds and infections. This narrative review aims to gather information and evidence supporting the role of HBOT in the treatment of SSIs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…HBO therapy, applied according to the Amsterdam Protocol, has been shown to be effective in limiting the incidence of wound infection and the spread of refractory infections. The ischemic environment after trauma and cell death poses a risk for the development of anaerobic infection [ 20 , 21 ]; HBOT promotes aerobic metabolism by providing a high supply of oxygen and resistance to anaerobic bacteria [ 22 ]. Delaying the start of HBO therapy is also associated with a significantly higher infection rate and highly complex reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…HBO therapy, applied according to the Amsterdam Protocol, has been shown to be effective in limiting the incidence of wound infection and the spread of refractory infections. The ischemic environment after trauma and cell death poses a risk for the development of anaerobic infection [ 20 , 21 ]; HBOT promotes aerobic metabolism by providing a high supply of oxygen and resistance to anaerobic bacteria [ 22 ]. Delaying the start of HBO therapy is also associated with a significantly higher infection rate and highly complex reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it has been reported that wild strains of Pseudomonads, Burkholderias, and Stenotrophomonads stopped growing under hyperbaric conditions at a pressure of 2.8 ATA of 100% oxygen [230]. HBOT is used as a primary or alternative method for the treatment of infections such as diabetic foot infection, surgical site infections, gas gangrenes, osteomyelitis, and necrotizing compartments [229]. In addition to the bactericidal effects, HBOT suppresses the production of clostridia alpha toxin in gas gangrene diseases.…”
Section: Ros Formation Induced By Antibacterial Hyperbaric Oxygen The...mentioning
confidence: 99%
“…Studies finalized to investigating the application of HBOT in treatment of different surgical site infections (SSI)[229].…”
mentioning
confidence: 99%
“…As a result, there is an increase in the formation of oxygen radicals, resulting in the elimination of anaerobic and facultative anaerobic microorganisms. 16 Besides, this process favours angiogenesis and the restoration of blood flow in the tissues. 17 Several factors should be considered as potential complications of the treatment, such as the patient's agreement, cooperation with the treatment and the degree of compromised bone.…”
mentioning
confidence: 99%